Analisis Pengaruh Financial Risk Terhadap Perkembangan Pasar Sukuk Di Indonesia Tahun 2012-2023 - Athallah, Naufal Alwan; Rahmawati, Farida (ITB AAS INDONESIA Surakarta, 2024)
This study aims to evaluate the impact of financial risks such as exchange rates, foreign debt, debt service ratio, current account, and international liquidity on the development of the sukuk market in Indonesia both in the short and long term. The data used for this study comes from Bank Indonesia and International Monetary Fund data during 2012 Q1-2023 Q4. The results of the Autoregressive Distributed Lag (ARDL) model show that in the short term, the exchange rate and international liquidity have a negative and significant influence on the development of state sharia securities. While the debt service ratio and current account have a positive and significant influence on the development of state sharia securities. In the long run, the exchange rate has a negative and significant influence, foreign debt and debt service ratio have a negative and insignificant influence, while the current account has a positive and significant influence on the development of Islamic securities. On the other hand, international liquidity has a positive and insignificant influence on the development of state Islamic securities.